PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PASAMAN KABUPATEN PASAMAN BARAT - Sintia, Lia; Aima, Zulfitri; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTThis research aimed to know the understanding of mathematic concept at eight grade junior high school students number 1 (one) in Pasaman Kabupaten Pasaman Barat by using active learning strategy with Learning type Starts With A Question is more better than conventional learning. Kind of this research is experiment research by design random of the subject. The population of this research is the students of eight grade junior high school number 1 (one) in Pasaman. The technique taked of the sample is random; the elected sample classes are VIII5 as experiment class and VIII6 as control class. Instruments that used in this research is final test in the form of an essay. Data that obtained in analysis by using normality test, homogenity test and t-test. Based on the result of hypothesis test by software MINITAB Â to obtained P-value = 0,006 smaller from Î± = 0,05, so the hypothesis of this research is accepted. So we can conclude that the studentâs understanding of mathematic concept by using active learning strategy with Learning Type Starts With A Question is more better than the studentâs understanding concept by conventional leaning at eight grade junior high school students number 1 (one) in Pasaman Kabupaten Pasaman Barat in academic year 2013/2014 with confidence level is 95%.Â